Dependence on the hydrological variability of macroclimatic phenomena: Case study: analysis of the relationship between the ocbevent and the water regime of the northern supply system of Bogotá - Arteaga Ávila, Lina Betulia; Delgado Peña, Lina Fernanda; Ivanova, Yulia (Ingeniería Solidaria, 2019)
Introduction: This article is the result of the investigation of the incidence of the quasi-global oscillation phenomenon on the water behavior in the north of Bogota supply carried out at the New Granada Military University in the year 2017.Problem: In the last decade in Colombia, years have been presented by very high and of very low relative humidity, which are associated with macroclimatological phenomena that have repercussions on the regional and local hydrological regime, generating variability of the water supply.Methodology: This study presents a statistical analysis that is prone to determine the influence of the quasi-biennial oscillation on the average monthly flows of the Sisga, Tominé and Neusa reservoirs of the north Bogotá supply system, based on linear correlations. between the two variables. Result: an incidence of the quasi-biennial oscillation phenomenon was observed on the tributaries to the reservoirs between 2.7% and 4.0%, which takes a nine-month period to reflect.Conclusion: The phenomenon of quasi-biennial oscillation does not significantly contribute to the surface runoff of the studied basins.Limitations: Although the study has not been able to demonstrate the incidence of the natural phenomenon, in other areas of the country this effect is demonstrated. As a hypothesis, it can be assumed that the application of other statistical methods different from the one applied, would allow a deeper analysis of the results.